Optimizing Idle Land Utilization to Enhance Local Food Security in Banjarbaru City - Rizali, Akhmad; Abbas, Saipul; Marsuni, Yusriadi; Sari, Yulia Padma; Farah, Nurin Nisa; Noorkomalasari, Noorkomalasari; Badaruddin, Badaruddin (Jurnal Biologi Tropis, 2025)
The ongoing land-use conversion in Banjarbaru City has significantly reduced agricultural areas, potentially threatening local food availability and the achievement of food security. This study aims to identify the distribution of idle land and assess its potential utilization as an alternative for agricultural development in urban areas. The methodology integrates drone imagery for mapping uncultivated land, agricultural and biophysical statistical data, and community perception surveys to evaluate readiness and constraints in managing idle land. The results show that idle lands are spread across all districts, with the highest concentration in South Banjarbaru and Landasan Ulin. These areas exhibit high potential for the development of horticultural crops and lowland rice cultivation, although technical interventions such as soil rehabilitation and improved water access are required. In conclusion, optimizing the utilization of idle land in Banjarbaru City can serve as an effective strategy to enhance local food production and strengthen area-based food security.